2011
DOI: 10.1186/1477-7525-9-21
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life among patients receiving palliative care in South Africa and Uganda: a multi-centred study

Abstract: BackgroundQuality of life (QOL) is a core outcome of palliative care, yet in African settings there is a lack of evidence on patients' levels of QOL. We aimed to describe QOL among patients with incurable, progressive disease receiving palliative care in South Africa and Uganda, to compare QOL in cancer and HIV, to determine how domains of QOL correlate with overall QOL, and compare levels of QOL in this population with those in other studies using the same tool.MethodsA cross-sectional survey was conducted us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 68 publications
4
67
0
Order By: Relevance
“…According to Selman et al (2011b), QoL assessment has become increasingly important in the developed world, supporting the following statement by McKinsey (Higginson et al, 2012): "If you can measure it, you can manage it." This drive to measure QoL is motivated by healthcare providers' attempts to understand how healthcare interventions influence the lives of patients rather than merely their physical outcomes.…”
Section: Introductionmentioning
confidence: 97%
“…According to Selman et al (2011b), QoL assessment has become increasingly important in the developed world, supporting the following statement by McKinsey (Higginson et al, 2012): "If you can measure it, you can manage it." This drive to measure QoL is motivated by healthcare providers' attempts to understand how healthcare interventions influence the lives of patients rather than merely their physical outcomes.…”
Section: Introductionmentioning
confidence: 97%
“…Over the past two decades, the important role of social mediators of women's health, including both the size and the composition of women's networks, has been emphasized in ethnographic and demographic studies (Adams, Madhavan and Simon, 2002; Haddad, Hoddinott and Alderman, 1997; Madhavan, 2002; Madhavan and Adams, 2003; Pick and Obermeyer, 1996; Simon, Adams and Madhavan, 2002). Thus, women's social connectedness has been linked to such outcomes as nutritional status (Ice et al ., 2011; Shayo and Mugusi, 2011), end of life care (Selman et al ., 2011), and protection against cognitive decline (Gureje et al ., 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Among 64 HIVĂŸ patients attending a hospice in South Africa, symptoms that may relate to existential concerns were highly prevalent; for example, loneliness (50%), hopelessness (42%), an increased sense of guilt or punishment (39%), and a decreased sense of usefulness (27%) [30]. In a previous article, we reported that PC patients in South Africa and Uganda judged feeling at peace and having a sense of meaning in life more important than physical comfort [31]. The importance of the spiritual domain in recognized in the African Palliative Care Association (APCA)'s core standards for PC [18], and spiritual care recommendations have recently been launched [32].…”
Section: What Is New?mentioning
confidence: 96%